FACTORS AFFECTING WORK EFFICIENCY OF EMPLOYEES IN NONTHABURI PROVINCIAL ADMINISTRATION ORGANISATION - Sirirat, Suphak; Sawangwong, Boonwat (PEOPLE: International Journal of Social Sciences, 2020)
The objectives of the research include: 1) to study the level of work motivation among employees of Nonthaburi Provincial Administration Organisation; 2) to study the efficiency of employees and; 3) to study factors affecting work efficiency of employees in Nonthaburi Provincial Administration Organisation. The sample group was 230 employees. It used questionnaire for data collection. Data analysis involved descriptive statistics such as percentage, mean, standard deviation and Multiple Regression Analysis at the significance level of 0.05. The study revealed that; 1) most employees of Nonthaburi Provincial Administration Organisation are female, age between 30 - 40 years old, and graduated with at least a bachelor degree. Their average monthly income is between 15,000 - 24,999 Baht. The length of employment goes between 5 - 10 years and they are mostly public servant; 2) the overall work motivation is at a high level; 3) performance efficiency on the overall is also in a high level; and 4) factors affecting work efficiency of employees in Nonthaburi Provincial Administration Organisation includes ‘personnel type’, ‘responsibility’, ‘pay’, ‘status in the organisation’ and ‘physical working condition.’